
PUMPA - SMART LEARNING
எங்கள் ஆசிரியர்களுடன் 1-ஆன்-1 ஆலோசனை நேரத்தைப் பெறுங்கள். டாப்பர் ஆவதற்கு நாங்கள் பயிற்சி அளிப்போம்
Book Free DemoThe natural numbers are 1, 2, 3, 4, …
We need to find the value of 1 + 2 + 3 + 4 + …. + n.
Consider the identity (x + 1)^{k + 1} - x^{k + 1}.
Since the sum of all the numbers is 1, put k = 1 in the above identity.
(x + 1)^{1 + 1} - x^{1 + 1} = (x + 1)^2 - x^2
= x^2 + 2x + 1 - x^2
= 2x + 1
(x + 1)^2 - x^2 = 2x + 1 - - - - (I)
Now, substitute x = 1, 2, 3, … n in equation (I).
When x = 1, 2^2 - 1^2 = 2(1) + 1
When x = 2, 3^2 - 2^2 = 2(2) + 1
When x = 3, 4^2 - 3^2 = 2(3) + 1
\vdots \vdots \vdots
When x = n - 1, n^2 - (n - 1)^2 = 2(n - 1) + 1
When x = n, (n + 1)^2 - n^2 = 2(n) + 1
Add all the above equations of x values.
2^2 - 1^2 + 3^2 - 2^2 + 4^2 - 3^2 + \cdots + n^2 - (n - 1)^2 + (n + 1)^2 - n^2 = 2(1) + 1 + 2(2) + 1 + 2(3) + 1 + \cdots + 2(n - 1) + 1 + 2(n) + 1
2^2 + 3^2 + 4^2 + \cdots + n^2 + (n + 1)^2 - (1^2 + 2^2 + 3^2 + \cdots + (n - 1)^2 + n^2) = 2(1) + 2(2) + 2(3) + \cdots + 2(n - 1) + 2(n) + (1 + 1 + 1 + ... n \ times )
By cancelling the same terms with opposite signs on the LHS, we get:
(n + 1)^2 - 1^2 = 2(1 + 2 + 3 + … + (n - 1) + n) + n
n^2 + 2n + 1^2 - 1^2 = 2(1 + 2 + 3 + … + (n - 1) + n) + n
n^2 + 2n = 2(1 + 2 + 3 + … + (n - 1) + n) + n
n^2 + 2n - n = 2(1 + 2 + 3 + … + (n - 1) + n)
n^2 + n = 2(1 + 2 + 3 + … + (n - 1) + n)
Therefore, .
Sum of first n natural numbers =
Important!
1. The sum of the first n natural numbers is also called a Triangular Number because they form triangle shapes.
2. The sum of squares of the first n natural numbers are also called Square Pyramidal Numbers because they form pyramid shapes with a square base.